Mechanics of Energy Absorption by Progressive Plastic Deformation of a Square Column with an Ellipsoidal Bulge Base - M. A., Hassan (Natural Science Publishing, 2014)
Thin-walled square columns are generally used as energy absorber in various applications due to their ease of fabrication and installation, high energy absorption capacity in terms of progressive plastic deformation and long stroke. However, the main drawback of a standard square column is the high initial peak force. An ellipsoidal bulge base is proposed to overcome this shortcoming and at the same time to improve the crush performance. Static axial crushing were performed by finite element analysis to determine the initial peak force (IPF), crush force efficiency (CFE) and plastic specific energy absorption (SEA) of columns having ellipsoidal bulge bases with various thicknesses. It was found that the bulge base significantly enhanced the column crush performance as well as the deformation characteristics. A comparison with the plain square column was carried out and it was found that the bulge base reduced the initial peak force and increased the crush force efficiency. A simple analytical approach is proposed to predict the reduction of initial peak force with the use of this trigger mechanism